Emerald and Aquamarine Mineralization in Canada - Groat, Lee; Hart, Craig; Lewis, Lara; Neufeld, Heather (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2005)
SUMMARY This paper reviews the geology, mineralogy, and origin of the gem varieties of beryl, including emerald (green) and aquamarine (blue); it focuses on western Canada, especially the Yukon Territory, because this is where most of the recent discoveries have been made. However, emerald occurrences in Ontario are also considered, including Canada's first reported discovery in 1940. Beryl (Be3Al2Si6O18) is relatively common and spatially associated with granites and granitic pegmatites, but emerald is rare because trace amounts of Cr and/or V are required (to replace Al in the crystal structure) and these elements generally do not occur in sufficient concentrations in granitic rocks. The geological conditions needed to bring Be into contact with Cr and/or V are briefly discussed, as are the factors to consider and techniques to use in exploring for gem-quality beryl.